A Conceptual Framework for Teaching English in TVET Environment - Mohd Shafeirul Zaman, Abd Majid; Azwin Arif, Abdul Rahim; Razmi, Ab Rahman; Zetti Adela, Zolkepli (Politeknik Sultan Haji Ahmad Shah, 2016)
TVET that has been highlighted in the Tenth Malaysia Plan aims to enhance the job opportunities for skilled employees. With the surplus amount of graduates today, the ability to master technical, vocational education and training is known to be an added value for individuals. In ensuring a ceaseless effort in promoting, doing intake and producing graduates under TVET, there must be a solid framework that can be used in the teaching and learning processes as the methodology in delivering the knowledge and information may be different from other mainstream. The new era of teaching and learning is through integration of ICT, which means that the centre of learning is on the students through acquiring the information on their own and presenting it in a discussion with the others. This digital classroom approach can be applied in the sense of teaching English language in TVET context. Students will be exploring for more knowledge and teachers will guide them in the learning process by introducing elearning platforms that can help to ease the flow through an interactive and engaging places to give and share ideas, thoughts, visual aids, and also discussions. Learning is no longer restricted to classroom but it goes beyond the expected environment where students can still interact with their teachers effectively after the normal learning session, not only with their educators but also with learners from over the world. This has somehow supports the globalized online learning principle that is to engage learners in a diverse learning environment.